SAT0239 T Cell CD80/Cd86 Co-Stimulatory Blockade Effectively Suppresses CD25 (+) in CD4 (+) T Cell Subpopulation but not the ACPA Titers in the Course of 48-Week Treatment of Patients with Rheumatoid Arthritis. (10th June 2014) - Murakami, M.; Ito, M.N.; Sekiguchi, M.; Matsui, K.; Kitano, M.; Imura, Y.; Ohmura, K.; Fujii, T.; Kuroiwa, T.; Maeda, K.; Morita, S.; Kawahito, Y.; et al.
Abstract : Background: Rheumatoid arthritis (RA) is a common immflamatory autoimmune disease characterized by persistent synovitis and progressive destruction of cartilage and bone in multiple joints. Among the autoantibodies detected in RA patients, circulating autoantibodies, anti-citrullinated protein/peptide antibodies (ACPA), are highly specific and useful diagnostic tools for RA. ACPA production seems to depend on antigen-specific CD4 (+) helper T cell activation. Activation of T cells requires costimulatory signals via binding of CD28 receptor with CD80/CD86 located on antigen-presenting cells (APC). Abatacept (ABA) is a biological agent for RA treatment, consisting of extracellular domains from cytotoxic T-lymphocyte antigen-4 and the Fc portion of human immunoglobulin G1 (CTLA-4-Ig) which competes with CD28 for CD80/86 binding. Objectives: This study aims to clarify how 48-week ABA treatment affects CD4 (+) T cell activation and ACPA production in RA patients. Methods: Peripheral blood mononucleated cells (PBMCs) and plasma were obtained from 30 patients enrolled in abatacept research outcome as a first-line biological agent in the real world (ABROAD study) at baseline, 24 and 48 weeks of ABA treatment. Fifty-three healthy individuals (HIs) were also enrolled as controls. Surface phenotypes and activation markers of T cells were analyzed with flow cytometory. ACPA titers were measured with EliA CCP ELISA kit. Results: Twenty-five patients (83.3%) were ACPA (+) (>4.5 U/mL). DAS28-CRP and SDAI were significantly reduced at 24 and 48 weeks compared with those at baseline. The proportion of CD25 (+) in CD4 (+) T cells in ACPA (+) group was significantly higher than those of ACPA (-) group and HIs at baseline (13.9±5.4% in ACPA (+) group; 6.7±2.9% in ACPA (-) group, p=0.0089 ; 7.1±4.6% in HIs, p<0.0001 ). The proportion of CD25 (+) in CD4 (+) T cells decreased at 24 and 48 weeks (13.9±5.4% at baseline; 6.6±5.8% at 24 weeks, p<0.0001 ; 6.1±3.1% at 48 weeks, p<0.0001 ). However, ACPA titers were not significantly changed at 24 and 48 weeks compared with those at baseline. Conclusions: 48-week T cell co-stimulation blockade reduces disease activities and the proportion of CD25 (+) in CD4 (+) T cells but not the ACPA titers in ACPA (+) RA patients. Disclosure of Interest: M. Murakami Speakers bureau: Bristol-Myers Squibb Japan, M. Ito: None declared, M. Sekiguchi Grant/research support: Bristol-Myers Squibb Japan, Speakers bureau: Bristol-Myers Squibb Japan, K. Matsui Grant/research support: Bristol-Myers Squibb Japan, M. Kitano Grant/research support: Bristol-Myers Squibb Japan, Y. Imura Grant/research support: Bristol-Myers Squibb Japan, K. Ohmura Grant/research support: Bristol-Myers Squibb Japan, T. Fujii Grant/research support: Bristol-Myers Squibb Japan, T. Kuroiwa: None declared, K. Maeda: None declared, S. Morita: None declared, Y. Kawahito Grant/research support: Bristol-Myers Squibb Japan, T. Mimori Grant/research support: Bristol-Myers Squibb Japan, H. Sano Grant/research support: Bristol-Myers Squibb Japan, N. Nishimoto Grant/research support: Bristol-Myers Squibb Japan DOI: 10.1136/annrheumdis-2014-eular.3997